Pricing Poseidon: Extreme Weather Uncertainty and Firm Return Dynamics - KRUTTLI, MATHIAS S.; TRAN, BRIGITTE ROTH; WATUGALA, SUMUDU W. (Journal of Finance, 2025)
ABSTRACT We empirically analyze firm‐level uncertainty generated from extreme weather events, guided by a theoretical framework. Stock options of firms with establishments in a hurricane's (forecast) landfall region exhibit large implied volatility increases, reflecting significant uncertainty (before) after impact. Volatility risk premium dynamics reveal that investors underestimate such uncertainty. This underreaction diminishes for hurricanes after Sandy, a salient event that struck the U.S. financial center. Despite constituting idiosyncratic shocks, hurricanes affect hit firms' expected stock returns. Textual analysis of calls between firm management, analysts, and investors reveals that discussions about hurricane impacts remain elevated throughout the long‐lasting high‐uncertainty period after landfall.